Excited-State Vibration-Polariton Transitions and Dynamics in Nitroprusside - Herrera-Urbina, F; Triana-Galvis, J (Nature Research, 2021)
Strong cavity coupling to molecular vibrations creates vibration-polaritons capable of modifying chemical reaction kinetics, product branching ratios, and charge transfer equilibria. However, the mechanisms impacting these molecular processes remain elusive. Furthermore, even basic elements determining the spectral properties of polaritons, such as selection rules, transition moments, and lifetimes are poorly understood. Here, we use two-dimensional infrared and filtered pump–probe spectroscopy to report clear spectroscopic signatures and relaxation dynamics of excited vibration-polaritons formed from the cavity-coupled NO band of nitroprusside. We apply an extended multi-level quantum Rabi model that predicts transition frequencies and strengths that agree well with our experiment. Notably, the polariton features decay ~3–4 times slower than the polariton dephasing time, indicating that they support incoherent population, a consequence of their partial matter character. © 2021, This is a U.S. government work and not under copyright protection in the U.S.; foreign copyright protection may apply.